Coastal Community Empowerment Strategy in Jember Regency - Kanthi Pangestuning Prapti (Journal of Aquaculture Science, 2021)
The high potential of the coastal village of Jember Regency needs to be followed up with development and development programs. Empowerment of coastal communities is one form of program actualization, which requires the participation of the coastal community itself and stakeholders. In the context of this thought, collective commitment from parties with potential resources is needed. This study aims to determine the potential of coastal resources and determine the strategy of empowering coastal communities based on the potential of coastal resources in the Jember Regency. The research method used is a descriptive method, with data analysis using SWOT analysis as the basis for determining the strategy of empowering coastal communities in Jember Regency through an intensive group discussion approach (Focus Group Discussion, FGD). The results of the SWOT analysis formulate, namely: 1) Increasing knowledge and technology in the community about the concept of coastal and community empowerment (especially community participation), 2) Improvement of road access to coastal areas (especially beaches) Jember Regency as well as several infrastructure facilities to support the development of coastal ecotourism, 3) Strengthening community group institutions as a step to optimize the management of joint business groups (KUB) on the coast of Jember Regency, 4) Development of fishing port facilities and infrastructure (fish landing sites), 5) Identification of potential coastal resources and sustainable coastal community needs, 6) Delineation of coastal areas between villages within the sub-district area, 7) Integration of coastal community empowerment programs between stakeholders (horizontally or vertically).Keywords: community empowerment, Jember coast.